Penerapan Pembelajaran di Luar Kelas Untuk Meningkatkan Pemahaman Kosakata Bahasa Inggris Kelas IV MI Maarif NU Klesman Mojotengah Wonosobo - Royani, Ni'matur Rizqiyani; Noor Aziz; Firdaus Firdaus (FKIP, Universitas Palangka Raya, 2024)
This article discusses the application of learning outside the classroom to improve English vocabulary comprehension in grade IV students at MI Maarif NU Klesman Mojotengah, Wonosobo. The purpose of this study is to improve students' English vocabulary comprehension skills through learning activities outside the classroom. The method used in this research is classroom action research conducted in several cycles. Each cycle consists of planning, implementing, observing, and reflecting. The data obtained in this study included observations, vocabulary tests, and questionnaires. The results showed that the application of learning outside the classroom was effective in increasing the fourth grade students' English vocabulary comprehension. Based on the findings of this study, it is suggested that English teachers at MI Maarif NU Klesman Mojotengah, Wonosobo, integrate more activities outside the classroom in learning English vocabulary. This will provide students with a more immersive learning experience and improve their overall English skills.